Geographical barriers to timely diagnosis of cystic fibrosis and anxiety level of parents during newborn screening in Turkey - AY, NADİYE PINAR; GÖKDEMİR, YASEMİN (WILEY, 2021)
Background Despite the availability of cystic fibrosis (CF) screening countrywide, diagnostic delay is still a crucial issue. The objectives of this study were to explore the stages of the NBS process, determine the risk factors associated with diagnostic delay and evaluate parent anxiety and experience throughout the process. Methods This is a multicenter cross-sectional study. A questionnaire was completed by parents of newborns diagnosed with CF via NBS in 17 centers. Socio-demographic characteristics, parent knowledge and experiences related to NBS, sweat test availability in the region of residence, and time to the definitive CF diagnosis were assessed through this questionnaire. Parents' anxiety levels were evaluated through the State-Trait Anxiety Inventory scales 1 and 2. Delayed diagnosis (DD) was defined as a definite CF diagnosis beyond the 8th week of life. Predictors of delayed CF diagnosis were evaluated by univariate and multivariate analysis. Results A total of 220 CF patients diagnosed via NBS were enrolled; 82 (37.3%) babies had DD. Multivariable analysis indicated that residence in the Southeast Anatolia region of Turkey (OR = 10.79, 95% CI = 2.37-49.2) was associated with a higher incidence of DD compared with other regions in Turkey. Of the total, 216 (98.1%) of the caregivers regarded the NBS program as useful and 180 (82%) reported high anxiety levels. Conclusion The organization of newborn screening should take into account regional and socio-cultural characteristics to improve the early diagnosis of CF and also reduce the anxiety level of parents.
Keywords: cystic fibrosis; late diagnosis; parent anxiety; AGE